Early Deterioration and Long-Term Prognosis of Patients With Intracerebral Hemorrhage Along With Hematoma Volume More Than 20 ml: Who Needs Surgery? - Lin, Fuxin; He, Qiu; Tong, Youliang; Zhao, Mingpei; Ye, Gezhao; Gao, Zhuyu; Huang, Wei; Cai, Lveming; Wang, Fangyu; Fang, Wenhua; Lin, Yuanxiang; Wang, Dengliang; et al. (Frontiers in Neurology, 2022)
Background and Purpose: The treatment of intracerebral hemorrhage (ICH) patients with moderate hematoma and without cerebral hernia is controversial. This study aimed to explore risk factors and establish prediction models for early deterioration and poor prognosis. Methods: We screened patients from prospective ICH registration database (RIS-MIS-ICH, ClinicalTrials.gov Identifier: NCT03862729). The enrolled patients had no brain hernia at admission, with hematoma volume more than 20ml. All patients were initially treated by conservative methods and followed up ≥ 1 year. A decline of Glasgow Coma Scale (GCS) more than 2 or conversion to surgery within 72h after admission was defined as early deterioration. Modified Rankin Scale (mRS) ≥ 4 at 1 year after stroke was defined as poor prognosis. The independent risk factors of early deterioration and poor prognosis were determined by univariate and multivariate regression analysis. The prediction models were established based on the weight of the independent risk factors. The accuracy and value of models were tested by ROC curve. Results: After screening 632 ICH patients, a total of 123 legal patients were included. According to statistical analysis, admission GCS (OR, 1.43; 95% CI, 1.18-1.74; P < 0.001) and hematoma volume (OR, 0.90; 95% CI, 0.84-0.97; P = 0.003) were the independent risk factors for early deterioration. Hematoma location (OR, 0.027; 95% CI, 0.004-0.17; P < 0.001) and hematoma volume (OR, 1.09; 95% CI, 1.03-1.15; P < 0.001) were the independent risk factors for poor prognosis, and island sign had a trend toward significance (OR, 0.50; 95% CI, 0.16-1.57; P = 0.051).The admission GCS and hematoma volume score were combined for an early deterioration prediction model with a score from 2 to 5. ROC curve showed area under the curve (AUC) was 0.778 and cut-off point was 3.5. Combining the score of hematoma volume, island sign, and hematoma location, a long-term prognosis prediction model was established with a score from 2 to 6. ROC curve showed AUC was 0.792 and cutoff point was 4.5. Conclusions: The novel early deterioration and long-term prognosis prediction models are simple, objective and accurate for ICH patients with hematoma volume more than 20ml.